Kuwait : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
The 2012 Article IV Consultation discusses the economic outlook for Kuwait for 2012, which is broadly positive. Economic recovery is expected to strengthen, led by high government expenditure-particularly wages and capital expenditure. High fiscal and external surpluses are expected to persist. Inflation is projected to moderate slightly owing to a decline in global food inflation. The authorities are encouraged to continue to be vigilant regarding existing and emerging risks, enhance investment companies' (ICs) supervision, and develop the needed tools for ICs resolution.